The Effect of Discount, Promotion, Hedonic Shopping Motivation, Shopping Lifestyle on Impulse Buying on Tiktok Shop Users - Komsi Koranti; Syntha Noviyana; Sriyanto Sriyanto; Nur Indah Aryani (PT Mattawang Mediatama Solution, 2024)
The purpose of this study is to determine the effect of discount, promotion, hedonic shopping motivation, shopping lifestyle on impulse buying in Tktok shop users and to determine the most dominant independent variables among variables, namely discount, promotion, hedonic shopping motivation, shopping lifestyle on impulse buying in tiktok shop users This research method uses primary data with the test stages carried out, namely validity test, reliability test, normality test, heteroscedasticity test, multicollinearity test, multiple linear regression, F test, t test and coefficient of determination. Data collection was carried out using a questionnaire instrument with data collected by 161 respondents. The sampling method in this study is non-probability sampling with purposive sampling techniques. The results of this study show that the variables discount, promotion, hedonic shopping motivation, and shopping lifestyle affect impulse buying. The most dominant variable in this study is the shopping lifestyle variable by looking at the value of the shopping lifestyle regression coefficient of 0.751.